Metode three lines of defense sebagai upaya pencegahan risiko pada industri perbankan syariah di Indonesia - Rahmawati, Zulfa Muasaroh Binti (Maliki Interdisciplinary Journal, 2024)
The Three Lines of Defense has evolved in recent years to encompass all banking activities, including Islamic banks. It not only focuses on financial aspects but also aims to strengthen its fundamental principles, broaden its scope, and elucidate the key roles within the organization to facilitate robust governance and risk management capabilities. In this study, researchers found that the application of principles of quality management, risk management, and a total quality management approach significantly reinforces all three lines of defense in operational risk management. To strengthen the first line of defense, which involves identifying and handling risks at the operational level, we suggest merging the roles of process owners and risk owners into one person or team responsible for managing both the processes and associated risks. These findings provide a deeper understanding of how the application of quality management and risk management principles, along with effective coordination, can strengthen the Three Lines of Defense model in the context of Islamic banking. The practical implications of these findings can assist Islamic banks in enhancing their governance and risk management practices to achieve sustainable success.